É assim que eu trabalho na Atenção Básica em Saúde: uma pesquisa-ação colaborativa com terapeutas ocupacionais em uma Comunidade de Prática - Demonari de Aguiar, Laysla (2025)
Primary Health Care (PHC) is characterized as the first level of health care, offering comprehensive care and taking place in the place closest to people's lives. In recent years, some problems have been added to the PHC context, causing direct impacts on work processes and the care offered to the population. Occupational therapists are present in PHC services, with generalist practices centered on people's needs. There is room to investigate the reality of occupational therapists' work in Brazilian PHC, in order to unveil work processes in the face of the repercussions of current management and funding policies on work in PHC and the care practices developed in this context. To this end, the community of practice is presented as a theoretical-methodological strategy that favors the integration of investigative and training aspects. In order to identify aspects of the reality of the work of occupational therapists in Brazilian PHC, an action research was carried out, operationalized as a Virtual Community of Practice/CoP, with 14 meetings held online and synchronously, lasting 1 hour and 30 minutes, during the months of April to October 2023. The meetings were videotaped and their transcripts analyzed thematically. Six occupational therapists took part, coming from different regional contexts, with a diversity of services, employment relationships and populations served. The results were organized in such a way as to present the participants expectations and how they shared their work in PHC, valuing the narrative process sustained by the exchange of knowledge and experiences through the sentence “this is how I work”. It was possible to identify aspects of the work process organized into three themes: 1. Where is the humanization policy? Overload and dehumanization; 2. I want to offer quality care, like what I was taught to do. The high demand for adaptability in work processes: caring for, managing and discussing cases; and 3. what to do with all these contingencies, revealing the repercussions of current management and funding policies on the participants' daily personal and work lives and health. The aspects relating to care practices were organized into four themes: 1. Challenges and dilemmas for occupational therapy care in PHC; 2. Expectations and desires for working in PHC; 3. Professional identity in occupational therapy; and 4. Care practices in occupational therapy in PHC. Care practices in occupational therapy in PHC, revealing the desire to work in PHC, the complexities of care and the ethics of care in PHC based on the specificity of occupational therapy and implicit practices. The aspects of participation in the virtual CoP can be understood both in their formative-reflective aspects and in the power of the care constructed, and these results were organized in such a way as to describe the meetings and organized into two themes: 1. The potential of a CoP to unveil occupational therapy work in PHC and 2. The CoP as a space for care. The original results of this research indicate that there are adverse conditions that impact professional practice and the various strategies adopted by occupational therapists to overcome difficulties in the workplace, as well as highlighting the CoP as a space for building knowledge and, at the same time, producing care.